Geomorphic design of alluvial channels for oil sands mine closure - Ade, F; Sawatsky, l; Beersing, A; Fitch, M (Mine Closure 2011: Proceedings of the Sixth International Conference on Mine Closure, 2011)
The design of mine closure alluvial channels in the Oil Sands Region (OSR) is typically based on the geomorphic approach which requires an understanding and characterisation of natural alluvial channels in the region for replication at mine closure. In 2005 and 2006, detailed geomorphic surveys were conducted at 54 representative stream reaches to collect channel dimensions, channel slope, sinuosity, bed material composition and instantaneous discharge. This dataset was augmented with data available in oil sands environmental reports and regional maps; and flow modelling results of the selected stream reaches and their basins. The resulting dataset was used to produce region-specific regime relationships relating dependent reach-averaged channel parameters for width, depth and slope to discharge. Relationships were also provided to reflect the variations in channel variable within a reach, and recommendations were provided for meander wavelength and meander belt width. Roughness caused by large woody debris and other obstructions such as active and inactive beaver dams was determined to have a significant effect on channel morphology. This effect can be mimicked, prior to beaver colonisation, by placing roughness elements across the constructed channels at specified intervals using a design tool developed for this purpose. A step by step design procedure for replicating natural analogues or using the regime approach is provided to assist in designing alluvial channels in OSR mine closure landscape.